Derivación de valores económicos de la producción de leche de bovinos en la parroquia San José de Poaló utilizando funciones de beneficio. - Puchaicela Ullco, Sara Narcisa (2023)
The assessment of the different genetic characteristics in the reproduction of dairy cattle has a main value for the beginning of a genetic improvement project focused on dairy cows, considering phenotypic and genotypic traits. Despite the fact that the minority producers of the San José de Poaló parish in their different farms do not have modernization and only act with their traditional knowledge, bearing in mind that they reduce their profitability as a result of poor selection of reproducers without having an estimate on the environment – genetics. Therefore, recognition of economic values is carried out in the parish aimed at minority milk producers, achieving that 12 farms enter to the genetic improvement project with 45 bovines. The production system managed in the sector is semi-stabled tied with a rope, mentioning that they do not have adequate land size for the number of animals they have, that is why they choose to use vacant lots and also they buy food, this create a raise in the cost of milk production/day, causing them to have no benefit. However, bovines must reach 1200 gr of weight/cow/day, but the data in the study showed that bovines acquire weight gain per day from 32,25 gr in calves to 1166,66 gr in adult bovines, these values reveal that the environment factor does affect feeding because in times of drought the animals do not acquire the ideal weight. The producers of the parish have an average of 1263,55 l/month with an average sale value of 0,40 cent., but to obtain large quantities of milk the producers must invest in the producing cows; the calculations showed that the average income within these months is $520,60, however the parish properties maintain expenses from $262 to $412 between the months of September to January, when performing the cost-benefit analysis, average values were obtained of $174,22.